2009
DOI: 10.1007/s00535-009-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between emergency and elective endoscopic sphincterotomy in patients with acute cholangitis due to choledocholithiasis: is emergency endoscopic sphincterotomy safe?

Abstract: Combination therapy comprising EBD plus EST as the initial treatment for patients with moderate acute cholangitis due to choledocholithiasis was safe and did not prolong the period of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
(28 reference statements)
0
17
0
1
Order By: Relevance
“…The incidence of post-EST pancreatitis is largely dependent upon the skill of the endoscopist, in addition to factors related to the host. Endoscopists must aim to improve their technique and fully utilize their abilities under an adequate guidance system [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of post-EST pancreatitis is largely dependent upon the skill of the endoscopist, in addition to factors related to the host. Endoscopists must aim to improve their technique and fully utilize their abilities under an adequate guidance system [25]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the hospital stay will be increased [141]. On the other hand, it has been reported that drainage, such as ENBD, is not required if stones are removed completely after EST in a one-stage procedure [142]. Short-term stenting is required to prevent cholangitis if any residual stones are suspected.…”
Section: Commentarymentioning
confidence: 99%
“…Additional studies have examined the adverse outcomes of subjects undergoing emergent versus elective ERCP, showing some increased incidence of pancreatitis in the emergent group. 18 Our study did demonstrate 15 complications of biliary decompression including summarized in table 5. There were no differences seen in complications between the quartiles.…”
Section: Discussionmentioning
confidence: 65%